2017
DOI: 10.1007/s10067-017-3612-y
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of TL1A are associated with disease activity in patients with systemic sclerosis

Abstract: TL1A is a member of the TNF superfamily. It performs significantly in the pathogenesis of rheumatic and autoimmune diseases partly through regulating the Th17 pathway. The clinical implication of circulating TL1A in patients with systemic sclerosis (SSc) remains unclear, and correlation between TL1A and Th17-related cytokines in the pathogenesis of SSc needs to be discussed. We measured serum levels of TL1A and Th17-related cytokines by ELISA in 47 patients with SSc, 56 patients with SLE, and 53 healthy subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…AS patients treated with anti-TNF monoclonal antibodies revealed strongly reduced serum levels of TL1A when compared with the patients without treatment (Konsta et al, 2013). In our previous studies, we found elevated serum levels of TL1A in lupus patients as compared with healthy controls and patients with systemic sclerosis (Xu, Chen, Li, Ren, & Ye, 2015;Xu et al, 2017). However, whether gene polymorphisms of TL1A are related to SLE susceptibility remains to be elucidated.…”
Section: Introductionmentioning
confidence: 79%
“…AS patients treated with anti-TNF monoclonal antibodies revealed strongly reduced serum levels of TL1A when compared with the patients without treatment (Konsta et al, 2013). In our previous studies, we found elevated serum levels of TL1A in lupus patients as compared with healthy controls and patients with systemic sclerosis (Xu, Chen, Li, Ren, & Ye, 2015;Xu et al, 2017). However, whether gene polymorphisms of TL1A are related to SLE susceptibility remains to be elucidated.…”
Section: Introductionmentioning
confidence: 79%
“…Elevated serum TL1A has been reported in an AS [31], and TNFSF15 polymorphisms have been suggested to be linked to the risk for SpA and AS [32,33]. Serum TL1A has previously been reported to be elevated in SLE and to a lesser extent, in systemic sclerosis [34,35], but it is difficult to compare the degree of elevation in serum TL1A across studies. The lack of consistent elevation of TL1A in patients with hepatitis C even in the presence of circulating immune complexes and/or RF suggests that there may be additional stimuli for TL1A production in RA, such as activation of Toll-like receptors by endogenous ligands in the joint [36].…”
Section: Discussionmentioning
confidence: 99%
“…146 Primary intestinal myofibroblasts express DR3 and functionally respond to direct TL1A signaling by increasing collagen. 146 In a recent study, TL1A overexpressing naïve 150 IL-17A is significantly overexpressed in CDstrictured areas compared with non-strictured areas. 151 In addition, IL-17A significantly inhibits myofibroblast migration and promotes the production of MMP-3, MMP-12, TIMP-1, and collagen by myofibroblasts from strictured CD tissues.…”
Section: Tl1amentioning
confidence: 91%
“…148 Th17 cell numbers and Th17related cytokines, including IL-17, IL-21 and IL-22, are significantly increased in active IBD. 150 IL-17A is significantly overexpressed in CDstrictured areas compared with non-strictured areas. 151 In addition, IL-17A significantly inhibits myofibroblast migration and promotes the production of MMP-3, MMP-12, TIMP-1, and collagen by myofibroblasts from strictured CD tissues.…”
Section: Il-17 and Th17 Cellsmentioning
confidence: 91%
See 1 more Smart Citation